Associations of serum 25‐hydroxyvitamin D with circulating PTH, phosphate and calcium in patients with primary hyperparathyroidism. (1st April 2013) - Jayasena, Channa N.; Modi, Manish; Palazzo, Fausto; De Silva, Akila; Donaldson, Mandy; Meeran, Karim; Dhillo, Waljit S.
Abstract: Background: Despite NIH clinical recommendations, many clinicians are reluctant to replace vitamin D in patients with hypercalcaemia with primary hyperparathyroidism (PHP) due to concerns over aggravating hypercalcaemia. Furthermore, the optimum level of vitamin D replacement in PHP remains unclear. Methods: We performed a large retrospective study to determine whether a relationship exists between serum 25‐hydroxyvitamin D levels, calcium and other important biochemical markers in patients with PHP. Serum, plasma and urinary biochemical measurements were collected from 251 patients with hypercalcaemia diagnosed with PHP. Results: When examining overall mean circulating levels during clinical follow‐up, serum 25‐hydroxyvitamin D correlated highly significantly with plasma parathyroid hormone (PTH) (r = −0·23, P  =   0·0003) and serum phosphate (r = 0·16, P  =   0·0119). No significant relationship was observed between serum calcium and 25‐hydroxyvitamin D (r = 0·002, P  =   0·98). Mean plasma PTH during clinical follow‐up was 51% lower in patients with serum 25‐hydroxyvitamin D > 60 nm when compared with patients who had 25‐hydroxyvitamin D < 20 nm ( P  <   0·01). Conclusions: Patients with PHP who have 25‐hydroxyvitamin D levels > 60 nm have significantly reduced PTH hypersecretion when compared with patients with deficient vitamin D levels, without exhibiting worse hypercalcaemia.